2018
DOI: 10.1186/s13039-018-0369-1
|View full text |Cite
|
Sign up to set email alerts
|

Parental origin of deletions and duplications – about the necessity to check for cryptic inversions

Abstract: BackgroundCopy number variants (CNVs) are the genetic bases for microdeletion/ microduplication syndromes (MMSs). Couples with an affected child and desire to have further children are routinely tested for a potential parental origin of a specific CNV either by molecular karyotyping or by two color fluorescence in situ hybridization (FISH), yet. In the latter case a critical region probe (CRP) is combined with a control probe for identification of the chromosome in question. However, CNVs can arise also due to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 36 publications
1
16
0
Order By: Relevance
“…As preferential maternal origin of recombinant chromosomes was already shown by Ishii et al (1997) this was not recapitulated in the present study. Similar effects are well known for small supernumerary marker chromosomes (Liehr 2006) and passing on of other kinds of chromosomal aberrations in human (Liehr et al, 2018). For clinical impact and impact of large and small to submicroscopic paracentric inversions, the latter being part of normal variance in humans, see Pettenati et al (1995); Liehr et al (2018) and database of genomic variants ().…”
Section: Introductionsupporting
confidence: 64%
“…As preferential maternal origin of recombinant chromosomes was already shown by Ishii et al (1997) this was not recapitulated in the present study. Similar effects are well known for small supernumerary marker chromosomes (Liehr 2006) and passing on of other kinds of chromosomal aberrations in human (Liehr et al, 2018). For clinical impact and impact of large and small to submicroscopic paracentric inversions, the latter being part of normal variance in humans, see Pettenati et al (1995); Liehr et al (2018) and database of genomic variants ().…”
Section: Introductionsupporting
confidence: 64%
“…Besides being a well-established routine test for the rapid detection of suspected microdeletion syndromes, FISH analysis can identify the position of duplicated loci in microduplication syndromes. Using specific locus probes, it is possible to identify cryptic balanced inversions in parents, resulting in CNVs arising in the offspring following meiotic recombination within the inversion segment of the carrier parent [42][43][44]. Thus, due to the wide range in its diagnostic capacity, array-CGH is a standard method in routine diagnostic multistep algorithm, where it serves as a first-tier test, confirmatory test or test following conventional G-banding karyotyping as well.…”
Section: Discussionmentioning
confidence: 99%
“…For constitutional genetics, it has recently been shown that FISH is the only routine diagnostic approach capable of detecting the parental origin of disease-causing submicroscopic inversions relevant for the offspring. Such submicroscopic events may lead to microdeletion or microduplication in the putative progeny of such inversion carriers [16]. Nonetheless, patients with a suspected microdeletion syndrome (including subtelomeric imbalances) are nowadays tested using molecular karyotyping rather than combination with cytogenetics.…”
Section: Chromosomes Visualized By Molecular Cytogeneticsmentioning
confidence: 99%
“…One example is the identification of recurrent microdeletion and -duplication syndromes by CMA collected in several databases (e. g., Decipher, ISCA, ECRUCA) and the identification of the underlying pathomechanism of nonhomologous recombination triggered by low copy repeats. Subsequently, predisposing rearrangements such as inversions were discovered in parents of affected individuals and are now the subject of evaluation in routine FISH diagnostics to estimate the recurrence risk for those families [16]. Even combining all available standard approaches in human genetic diagnostics may be insufficient to solve the disease-causing gene.…”
Section: Interim Conclusion For Researchmentioning
confidence: 99%